To study changes in corneal thickness and corneal endothelial cell density after phacoemulsification cataract surgery - Pardasani, Rajiv; Lohiya, Sohan (International Journal of Psychosocial Rehabilitation, 2020)
Cataract is common cause of diminution of vison. Myopia can be related to cataract. The common surgery of cataract performed is Phacoemulsification with the placement of a intraocular lens in posterior chamber. With the newer devices like specular microscopy, we can add to the existing literature. To study and compare thickness of central corneal (CCT) earlier and later of phacoemulsification surgery. To study and compare endothelial cell density (ECD) earlier and later of phacoemulsification surgery. A observational cross sectional study with 120 patients will be conducted in hospital based setting utilizing the data of patients eye. The relationship between preoperative and post-operative findings of CCT and ECD will be analysed by using specular microscopy. the mean ECD is expected to be lower than that of preoperative value and the mean CCT is expected to be higher than pre-operative value. The Pearson correlation test will be used to compare findings of ECD and CCT preoperative and postoperative. The primary result which is to be calculated will be change in corneal ECD (cells per square millimetre of the corneal surface) which is expected to be decreased. The central corneal thickness (CCT) will be calculated in micro meter is the another result which is expected to be increased.